2007
DOI: 10.1111/j.1365-2222.2007.02792.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro immunomodulation of Der p 1 allergen‐specific response by Lactobacillus plantarum bacteria

Abstract: In vivo co-administration of probiotic LAB with Der p 1 might prevent the development of the mite allergic response. The probiotic L. plantarum was shown to display in vitro therapeutic potentials for the treatment of allergy and to trigger the immune system by a TLR2- and MyD88-dependent signalling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 47 publications
2
53
2
1
Order By: Relevance
“…TLR2 and TLR4 are expressed at the cell surface, while TLR9 is expressed in endosomes (34). Recently, the specific TLRs involved in LAB recognition and cytokine production by DCs and macrophages have been identified (35)(36)(37)(38). Rigaux et al have reported that IL-12p40 secretion by mouse DCs in response to L. plantarum NCIMB8826 was dependent on TLR2-and TLR9-mediated signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…TLR2 and TLR4 are expressed at the cell surface, while TLR9 is expressed in endosomes (34). Recently, the specific TLRs involved in LAB recognition and cytokine production by DCs and macrophages have been identified (35)(36)(37)(38). Rigaux et al have reported that IL-12p40 secretion by mouse DCs in response to L. plantarum NCIMB8826 was dependent on TLR2-and TLR9-mediated signaling (37).…”
Section: Discussionmentioning
confidence: 99%
“…42,43 This modulation occurs either by the promotion of Th1-type responses 44 or by the induction of regulatory cells and cytokines. 20,45 Using a gnotobiotic mouse model, we showed that colonization with Lmix reduced the serum levels of the Th2-related Bet v 1-specific IgE and IgG1 antibodies as well as the Th1-related IgG2a antibody, implicating the involvement of regulatory mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Schiffrin et al [12] and Gill et al [13] evaluated the effects of two different probiotics in healthy adults, but these studies did not have a placebo group. Efforts trying to compare the in vitro results of one probiotic to its results in an in vivo setting are even more scarce and are at the moment limited to comparisons between in vitro and experimental animal studies [14][15][16] .…”
Section: Probiotic Intervention Has Strain-specific Anti-inflammatorymentioning
confidence: 99%